Performance assessment in elite football players: field level test versus spiroergometry - Broich, H.; Sperlich, B.; Buitrago, S.; Mathes, S.; Mester, J. (Journal of Human Sport & Exercise, 2012)
The purpose of this study was to demonstrate that elite football players with the same anaerobic threshold calculated from the lactate performance curve during a field level test may have substantially different values describing endurance performance capacity determined from spiroergometric laboratory tests. A group of 28 male elite football players underwent a field level test and a spiroergometric laboratory test. A subgroup of players with the same anaerobic threshold was selected, and the endurance performance capacity obtained from spiroergometric measurements during treadmill level tests were compared descriptively within this subgroup. Among the three players with the same anaerobic threshold, test duration for the treadmill level test and consequently also the maximal lactate value achieved during the test varied substantially. The tests were aborted after 5 min at 4.4, 4.8 and 4.0 m/s for players 1, 2 and 3, respectively. VO2-values at V4 were 87 %, 75 % and 96 % of their personal VO2-peak, respectively. Maximum lactate concentrations were 8.8, 9.2 and 5.3 mmol/L, respectively. Peak relative VO2 values were 55.0, 61.6 and 59.7 ml/min·kg, respectively. The result of this study clearly show that conventional field level tests yield insufficient information on underlying physiological and metabolic mechanisms of endurance performance capacity. Taking result of spiroergometric tests into account is critical for designing and evaluating player-specific training programs aimed at optimizing each player`s performance.